Новые и малоизвестные виды семейства Eurytomidae (Hymenoptera, Chalcidoidea) в фауне СССР - Зерова, М.Д. (Вестник зоологии, 1972)
В статье приводятся описания двух новых и одного неизвестного до сих пор в фауне СССР видов эуритомид. Описание Bruckophagus seravschanicus sp. n. и переписание Eurytoma laricis Y а n о даются по материалам, хранящимся в коллекции Зоологического института АН СССР (Ленинград). Описание Ahtola paludicola sp. n. дано по сборам автора, находящимся в коллекции Института зоологии АН УССР (Киев). Description of two new Eurytomid species is given in the paper. Bruchophagus servaschanicus sp. n. is bred from seeds of Onobrychis seravchanica B. F e d t s с h. from the Middle Asia. This species differs from the all known Bruchophagus species in its well developed middle furrow on propodeum. Holotype is in collection of the Zoological Institute of the Academy of Sciences of the USSR (Leningrad). Ahtola paludicala sp. n. is bred from galls on Schoenoplectus mucrotiatus (L.) P a l l a (Cyperaceae) from the Chernomorsky reservation (Kherson). This species is distinguished by its great size, long flagellum in both sexes and the structure of abdominal tergits in female. Holotype is in the Zoological Institute of the Academy of Sciences of the Ukrainian SSR (Kiev). Besides that the redescription of Eurytoma laricis Y a n o is given. This species formerly was not known in the Russian fauna. According to the materials presented in the collection of the Zoological Institute of the Academy of Sciences of the USSR it was found out that Eurytoma laricis is widely distributed in the USSR and develops in seeds of Larix dahurica T u г с z., L. sibirica L d b., L. pendula S.